Macbeth : a play by William Shakespeare - Hinds, Gareth, 1971-; Shakespeare, William, 1564-1616. (Somerville, Massachusetts : Candlewick Press, 2015)
"Macbeth, a general in the king's army, is returning from battle when he comes upon three witches who tell him that one day he'll be king. At first Macbeth dismisses their predictions, but an evil seed takes root in his mind, and soon he is convinced and impatient. At the urging of his wife, he resolves to take the throne by the most direct path: a dagger in the heart of King Duncan. But 'blood will have blood,' and when others grow suspicious of his sudden rise to power, is Macbeth prepared to commit more murder to keep the crown?"--Front flap.
Young Adult.
Keywords: Macbeth, -- King of Scotland, -- active 11th century -- Comic books, strips, etc; Shakespeare, William, -- 1564-1616 -- Adaptations; Kings and rulers -- Succession -- Comic books, strips, etc; Regicides -- Comic books, strips, etc; Kings and rulers -- Comic books, strips, etc; Scotland -- Comic books, strips, etc; Graphic novels